Graphical Illustration of Interaction Effects in Binary Choice Models: A Note. (15th December 2017) - Franken, Jason R.V.; Pennings, Joost M.E.; Garcia, Philip
Abstract: Graphing procedures for evaluating power or interaction terms in binary logit and probit models are illustrated in an application to hog producers' decisions based on transaction cost economics' hypothesised positive effect of the interaction of uncertainty and asset specificity on contract use. Results support the hypothesis, particularly for producers that are otherwise on the cusp (near the 50/50 probability) of choosing either contract or spot transactions based on their responses for other variables. Such insights may not be drawn without use of the demonstrated graphing procedures.